The Correlation between Students’ Motivation and Their English Speaking Ability - Anwar Rahman; Rafista Deviyanti (Politeknik Negeri Lampung, 2012)
The research is aimed at investigating the correlation between students’ motivation and their English speaking ability. The research samples were thirty-six first year students of SMAN 2 Bandar Lampung that were randomly selected by using lottery. Students’ motivation scores were calculated by using four-Likert-scale questions and their English speaking ability was tested by using transactional speaking test using criteria proposed by Heaton (1991). The results of motivation questionnaire showed that the highest score was 145 and the lowest score was 77 with the average of 111. 4. It was found out that 5. 5% students have high motivation, 60. 5 % students have average motivation, and 25% students have low motivation. It means that most of the students have good motivation. English speaking test scores showed that the average of students’ English speaking ability was 80.2 with the highest score of 90 and the lowest score of 73. It can be concluded that the students have very good ability in speaking English.The results showed that the coefficient correlation was 0.780 and it was significant where r-value of 0.780 was larger than the r-table of 0.334. It was also found out that motivation influenced English speaking ability with the score of 60.8 %. This means that motivation as a psychological factor has a positive correlation with English speaking ability. Students who had high level of motivation did more efforts and had more determination to reach their goals. On the contrary, students who had low level of motivation did not do more efforts in learning and in achieving their goals so that their speaking ability was low. Keywords: motivation, English speaking ability, correlation